THE ANALYSIS OF PARENTAL INVOLVEMENT TOWARDS STUDENTS’ LITERACY DEVELOPMENT IN SEKOLAH DASAR NEGERI 1 BANJAR - Regita, Ardia Pramesti (Universitas Pendidikan Ganesha, 2020)
This research aimed to analyze parental involvement in developing students’ literacy development in Sekolah Dasar Negeri 1 Banjar. The purpose of this study was to analyze how can parents support child’s literacy development and to identify the barriers to parental involvement. The subject of this study was the parents who had a low-educational attainment. This study was a descriptive qualitative. The data were collected by using two instruments namely questionnaire and interview guide. The instrument validity condcuted by expert judgement. The data obtained were descriptively analyzed. The findings of this study show that parents commonly did 16 activities in developing students’ literacy development. Moreover, Mother commonly accompanied their children in the reading activity at home. Parents usually use balinese language Furthermore, there were 13 barriers faced by the parents involvement.